COMPARISON BETWEEN CRANIAL THORACIC INTERVERTEBRAL DISC HERNIATIONS IN GERMAN SHEPHERD DOGS AND OTHER LARGE BREED DOGS. Issue 2 (26th December 2012) - Gaitero, Luis; Nykamp, Stephanie; Daniel, Rob; Monteith, Gabrielle
<x xml:space="preserve">Abstract</x> Cranial thoracic intervertebral disc herniations have been reported to be rare in dogs due to the presence of the intercapital ligament, however some studies have proposed they may not be uncommon in German Shepherd dogs. The purpose of this retrospective study was to compare cranial thoracic intervertebral disc herniations in German Shepherd dogs and other large breed dogs (control group). Medical records at the Ontario Veterinary College were searched for German Shepherd dogs and other large breed dogs that had magnetic resonance imaging studies including the T1‐T9 region. For each dog and each disc space from T1‐T9, three variables (compression, disc degeneration, and herniation) were recorded and graded based on review of sagittal T2‐weighted images. Twenty‐three German Shepherd dogs and 47 other large breed dogs met inclusion criteria. The German Shepherd dog group had higher scores than the control group for compression (P = 0.0099) and herniation (P < 0.001), but not disc degeneration (P = 0.97). In the German Shepherd dog group, intervertebral discs T2‐T3 and T4‐T5 had an increased risk for compression and T3‐T4 had an increased risk for compression and herniation. Findings from this study indicated that German Shepherd dogs may be more likely than other large breed dogs to have spinal cord compression due to cranial thoracic disc herniations. Imaging of the cranial thoracic spine, including T2‐T3, is recommended for German Shepherd dogs with T3‐L3 neurological signs.